Study on TB patients WHO defaulted treatment at chest clinic-Kurunegala - Herath, H.M.P.B (My University, 1993)
This study was carried out to determine the associated factors with drug defaulting by tuberculosis patients. Result of this study was aimed at predicating the possible defaulters at the beginning of treatment and to take the necessary precautions to minimize such "dropouts" in the future